2016
DOI: 10.1371/journal.pone.0148785
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Cerrado Biome (Neotropical Savanna) Soils

Abstract: The Cerrado, the largest savanna region in South America, is located in central Brazil. Cerrado physiognomies, which range from savanna grasslands to forest formations, combined with the highly weathered, acidic clay Cerrado soils form a unique ecoregion. In this study, high-throughput sequencing of ribosomal RNA genes was combined with shotgun metagenomic analysis to explore the taxonomic composition and potential functions of soil microbial communities in four different vegetation physiognomies during both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 56 publications
4
28
0
2
Order By: Relevance
“…Although chromatographic data revealed relatively high concentrations of methane in these soil samples, only 2% of all archaeal sequences were affiliated to the methanogenic organism Methanosarcina acetivorans, while 56% of all archaeal sequences detected were classified as uncultivated Crenarchaeota and 42% were affiliated to the Thaumarchaeota Candidatus Nitrososphaera gargensis. As observed for other soils [99, 117], archaeal richness and diversity values were significantly lower than those found for bacteria in the sedimentary soils from this petroliferous basin [118]. In another study, the effect of petroleum contamination on microbial communities from Trindade Island coastal soils were analyzed by microcosm experiments [119].…”
Section: Archaea In Soilsmentioning
confidence: 84%
See 2 more Smart Citations
“…Although chromatographic data revealed relatively high concentrations of methane in these soil samples, only 2% of all archaeal sequences were affiliated to the methanogenic organism Methanosarcina acetivorans, while 56% of all archaeal sequences detected were classified as uncultivated Crenarchaeota and 42% were affiliated to the Thaumarchaeota Candidatus Nitrososphaera gargensis. As observed for other soils [99, 117], archaeal richness and diversity values were significantly lower than those found for bacteria in the sedimentary soils from this petroliferous basin [118]. In another study, the effect of petroleum contamination on microbial communities from Trindade Island coastal soils were analyzed by microcosm experiments [119].…”
Section: Archaea In Soilsmentioning
confidence: 84%
“…Recently, high-throughput sequencing of ribosomal markers and shotgun metagenomic analyses were combined to investigate bacterial, fungal, and archaeal communities in soils of four different phytophysiognomies from Cerrado during the dry and rainy seasons [99]. Most of the archaeal sequences detected in soils from three vegetation physiognomies (Campo Sujo, Cerrado sensu stricto and Mata de Galeria) in both seasons were affiliated to Crenarchaeota and classified as Thermoprotei.…”
Section: Archaea In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity index values suggested by Ferreira de Araujo et al, 41 were higher than the ones shown by 53. Pereira de Castro et al, 42 and a higher fungal diversity was observed in campo graminoide than in Cerrado forests. In addition, several studies have shown that structural changes in the fungal community were in response to different soil managements.…”
mentioning
confidence: 91%
“…The physical, chemical and biological attributes of the soil are affected by several conditions related to the type of soil preparation used in each management system; the effects on these attributes are dependent on the intensity of soil disturbance, traffic of farm tractors, type of equipment used, management of plant waste, and moisture conditions in the soil at the time of tillage [8]. Despite previous findings in areas of the Cerrado biome [9][10][11], there is a lack of information about the impact of soil agricultural management on the fungal microbial community in Cerrado areas.…”
Section: Introductionmentioning
confidence: 99%